Parodontgel® on Wound Healing and Patient-Reported Outcome Measures (PROMs) after Tunneled Coronally Advanced Flap (TCAF) - Leonardo Mancini; Vincenzo Mancini (Case Reports in Dentistry)
The adjunctive use of healing gels following periodontal plastic surgery is not common in clinical practice, and no definitive benefits have yet been demonstrated. Case Presentation. A 33-year-old male patient with a central lower incisor class RT1 recession sought treatment due to sensitivity and dissatisfaction with the appearance of his smile. The patient had no history of periodontal disease; however, he was under orthodontic treatment contributing to the gingival recession and irregular gum contours. Treatment. The patient underwent two sequential surgical procedures. Initially, an apically repositioned flap (APF) was performed to correct the frenulum reducing flap tension and improving the gum line aesthetics. Subsequently, after 8 weeks, a tunneled coronally advanced flap (TCAF) was executed to further refine the gum contours and achieve root coverage. Postoperative Healing Protocol. To enhance the healing process and alleviate postoperative discomfort, a healing gel containing hyaluronic acid as the active molecule was applied to the surgical sites. The gel was expected to reduce pain perception and minimize the need for painkiller intake during the critical first week of recovery. The patient was asked to fill a pain chart for the initial 7 days, recording pain levels on a visual analogue scale (VAS 0-10) and the number of paracetamol tablets taken as painkillers. Results. After both the APF and TCAF surgeries, the patient reported pain levels with a mean VAS score of 4.33 and 4.25, respectively. The painkiller intake during the first week was noted to be 3 tablets for the APF and 2 tablets for the TCAF. Notably, the application of the healing gel with hyaluronic acid did not cause any adverse reactions, indicating its potential safety and efficacy in this context. Conclusion. The application of a healing gel containing hyaluronic acid after periodontal plastic surgery showed promising results in reducing postoperative pain and the need for painkillers during the initial week of recovery. However, further investigations through randomized clinical trials are required to establish the potential benefits and broader applicability of such healing gel applications in the context of periodontal plastic surgery.